2011
DOI: 10.1097/cej.0b013e32834761a6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of BRCA1 gene associated with demographic and pathologic factors in sporadic breast cancer

Abstract: Breast cancer (BC) is a leading cause of cancer-related deaths among women worldwide, and this study further demonstrates that the women of Varanasi (north India) are not untouched by this fatal disease. During BC development, epigenetic activity plays a key role in silencing gene expression. Its widespread occurrence in the cancer genome could inactivate many cellular pathways including DNA repair, cell cycle control, apoptosis, cell adherence, and detoxification. In this study, our aim was to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
2
3
1
Order By: Relevance
“…In addition, no association between BRCA1 methylation and premenopausal status was observed in our study. This was inconsistent with a previous report 43 which showed that BRCA1 -methylated breast cancers tended to occur at an early age (<50 years) and were more frequently observed in premenopausal or perimenopausal women than postmenopausal women. Furthermore, our results showed that BRCA1 promoter methylation was strongly related to breast cancer patients with high histological grade and lymph node metastasis, revealing that aberrant methylation of BRCA1 promoter may be implicated in the invasion and metastasis of breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, no association between BRCA1 methylation and premenopausal status was observed in our study. This was inconsistent with a previous report 43 which showed that BRCA1 -methylated breast cancers tended to occur at an early age (<50 years) and were more frequently observed in premenopausal or perimenopausal women than postmenopausal women. Furthermore, our results showed that BRCA1 promoter methylation was strongly related to breast cancer patients with high histological grade and lymph node metastasis, revealing that aberrant methylation of BRCA1 promoter may be implicated in the invasion and metastasis of breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…As expected from previous studies 14 29 43 , we demonstrated that there was a remarkable correlation between BRCA1 promoter hypermethylation and breast tumors with lack of ER and PR expression. However, no inverse relationship was found between BRCA1 methylation and Her2 status.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Bediaga et al and Holm et al have recently reported specific methylation patterns associated with distinct molecular subtypes of breast cancer [34,35]. Our findings are in agreement with those studies which have reported higher methylation of other genes like BRCA1 in triple-negative subtype indicating higher epigenetic dysregulation in these cancers [36,37].…”
Section: Discussionsupporting
confidence: 96%
“…Population differences in breast cancer characteristics were previously described in terms of pathological parameters (27,31,32), and in terms of the identification of mutations, intronic variant sequences and unclassified variants, as well as variated copy numbers, reporting a role in breast cancer susceptibility that remains to be clarified. For instance, mutations in the predisposition genes BRCA1 and BRCA2, known to be associated with hereditary breast cancer, were studied in different populations such as Sudanese (33,34), Tunisian (35), Indian (36) and Slovak (37), where population-specific genetic disorders were observed. Similarly, the Mspl polymorphism in the 3'-non-coding region of the CYP1A1 gene was associated with breast cancer in African-American but not in Caucasian women (38).…”
Section: Discussionmentioning
confidence: 99%